Flash 3D Imaging of Far-Field Dynamic Objects: An EMCCD-Based Polarization Modulation System - Shengjie Wang; Xiaojia Yang; Donglin Su; Weiqi Cao; Xianhao Zhang (Sensors, 2025)
High-resolution 3D visualization of dynamic environments is critical for applications such as remote sensing. Traditional 3D imaging systems, such as lidar, rely on avalanche photodiode (APD) arrays to determine the flight time of light for each scene pixel. In this context, we introduce and demonstrate a high-resolution 3D imaging approach leveraging an Electron Multiplying Charge Coupled Device (EMCCD). This sensor’s low bandwidth properties allow for the use of electro-optic modulators to achieve both temporal resolution and rapid shuttering at sub-nanosecond speeds. This enables range-gated 3D imaging, which significantly enhances the signal-to-noise ratio (SNR) within our proposed framework. By employing a dual EMCCD setup, it is possible to reconstruct both a depth image and a grayscale image from a single raw data frame, thereby improving dynamic imaging capabilities, irrespective of object or platform movement. Additionally, the adaptive gate-opening range technology can further refine the range resolution of specific scene objects to as low as 10 cm.